EFEKTIVITAS PEMBELAJARAN APLIKASI EDUCAPLAY TERHADAP MOTIVASI BELAJAR PADA PEMBELAJARAN PAI - Halimatus Sa'diyah; Syamsuri Ali; Beti Susilawati; Baharudin Baharudin (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
The low motivation to learn Islamic Religious Education (PAI) at SMK IT ICERA Babatan, caused by the lack of learning media innovation, is the background of this research. The main focus of the study is to evaluate the effectiveness of the use of the Educaplay application in increasing student learning motivation. This research uses a quantitative method with a quasi-experimental design of the nonequivalent control group type. The research stages include data collection through a motivation questionnaire that has been tested for validity and reliability, followed by data analysis using an independent t-test through SPSS software. The research findings show a significant difference between the experimental and control classes, where the t-value is 4.244 with a significance level of 0.000 < 0.05. These results prove that students who use Educaplay have a level of motivation, especially on the material relevance indicator, which is much better than the conventional learning group. The main conclusion confirms that the integration of interactive digital technology such as Educaplay is very effective as an innovative strategy to enliven the atmosphere of the PAI class and help students understand the connection of the material to real life. Practically, this study recommends educators to adopt educational game-based media to optimize student active engagement. The theoretical contribution of this research enriches the literature on the use of digital media in strengthening the affective aspects of students at the vocational high school level in a sustainable and measurable manner in the future to answer the challenges of modern education. ABSTRAK Rendahnya motivasi belajar Pendidikan Agama Islam (PAI) di SMK IT ICERA Babatan yang disebabkan oleh kurangnya inovasi media pembelajaran melatarbelakangi penelitian ini. Fokus utama kajian adalah mengevaluasi efektivitas penggunaan aplikasi Educaplay dalam meningkatkan dorongan belajar siswa. Penelitian ini menggunakan metode kuantitatif dengan desain quasi eksperimen tipe nonequivalent control group design. Tahapan penelitian meliputi pengumpulan data melalui angket motivasi yang telah diuji validitas dan reliabilitasnya, dilanjutkan dengan analisis data menggunakan independent t-test melalui perangkat lunak SPSS. Temuan penelitian menunjukkan perbedaan signifikan antara kelas eksperimen dan kontrol, di mana nilai t-hitung sebesar 4,244 dengan taraf signifikansi 0,000 < 0,05. Hasil ini membuktikan bahwa siswa yang menggunakan Educaplay memiliki tingkat motivasi, khususnya pada indikator relevansi materi, yang jauh lebih baik dibandingkan kelompok pembelajaran konvensional. Simpulan utama menegaskan bahwa integrasi teknologi digital interaktif seperti Educaplay sangat efektif sebagai strategi inovatif untuk menghidupkan suasana kelas PAI dan membantu peserta didik memahami keterkaitan materi dengan kehidupan nyata. Secara praktis, penelitian ini merekomendasikan pendidik untuk mengadopsi media berbasis permainan edukatif guna mengoptimalkan keterlibatan aktif siswa. Kontribusi teoretis penelitian ini memperkaya literatur mengenai pemanfaatan media digital dalam memperkuat aspek afektif siswa pada jenjang sekolah menengah kejuruan secara berkelanjutan dan terukur di masa depan guna menjawab tantangan pendidikan modern.